Delay-based load-balancing routing (DLBR) algorithm for wireless ad-hoc networks - Habib, I. (Institute of Electrical and Electronics Engineers Inc., 2015)
The shortest path routing does not balance the routing load on the links according to their capacity thus some links experience more traffic than they can accommodate, which congests the network. Hence there is a need to balance the traffic load on all links according to their capacities. By combining physical layer capacity with MAC layer estimated congestion value, a new delay-based load-balancing routing (DLBR) algorithm is proposed in this paper. A new routing metric i.e. The end-to-end delay (EED) is introduced, which estimates the congestion level at the MAC and physical layers. The DLBR then uses this metric to select high capacity links for data forwarding, thus providing paths with less congested nodes and high capacity links. Simulations have been conducted on MATLAB to study the performance of DLBR. Results show that for the same network load, DLBR outperforms the shortest path in terms of the average delay and packet loss. Â© 2015 IEEE.